Curriculum Integration’s Model in Arabic Language Education and Da’wah: A Case Study at STAI Ali bin Abi Thalib Surabaya - Mubarak Bamualim; Angger Bimantara; Iqbal Gogari (STAI Ali bin Abi Thalib Surabaya, 2026)
This research aims to describe the implementation and challenges of integrating the Arabic Language Education and Da’wah curricula at STAI Ali bin Abi Thalib Surabaya, with the expectation that graduates will possess both linguistic competence and the ability to perform missionary work in a scholarly and communicative manner. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, academic observations, and a review of curriculum documents and Semester Learning Plans (RPS). The findings reveal that curriculum integration is applied thematically across linguistic and Islamic fields, where Arabic is taught not only as a linguistic discipline but also as a medium to strengthen students' syar’i values. However, challenges such as limited human resources, a lack of faculty training in integrative curriculum design, and a shortage of innovative learning media persist. This study contributes to the discourse on curriculum integration in Arabic language and da’wah, also offers a practical reference for designing curricula that integrate Arabic language and da’wah skills. Consequently, this study recommends strengthening faculty capacity through specialized training, developing teaching materials that blend language and da’wah aspects, and optimizing internal academic coordination to ensure the sustainable application of this integrative curriculum. This study reveals that the integration of the Arabic Language Education and Da’wah curriculum at STAI Ali bin Abi Thalib Surabaya has been implemented through a thematic approach employing a connected curriculum model that facilitates inter-course linkage. The findings indicate that this model is effective in enhancing students’ linguistic and da’wah competencies, despite challenges related to the heavy credit load and the need for further development of lecturers’ professional capacities.